2019
DOI: 10.1098/rspb.2018.2733
|View full text |Cite
|
Sign up to set email alerts
|

Survival of retinal ganglion cells after damage to the occipital lobe in humans is activity dependent

Abstract: Damage to the optic radiations or primary visual cortex leads to blindness in all or part of the contralesional visual field. Such damage disconnects the retina from its downstream targets and, over time, leads to trans-synaptic retrograde degeneration of retinal ganglion cells. To date, visual ability is the only predictor of retinal ganglion cell degeneration that has been investigated after geniculostriate damage. Given prior findings that some patients have preserved visual cortex activity for stimuli pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 38 publications
4
28
0
1
Order By: Relevance
“…Two blindsight positive patients (P6, P8) showed retained fMRI signal in the blindsight test zone using both MP and pRF techniques, albeit not completely normal. This is consistent with previous studies ( Papanikolaou et al, 2014 ; Schneider et al, 2019 ; Sanchez-Lopez et al, 2020 ), and suggests that both methods can reveal preserved visual processing in hemianopia beyond SAP. Interestingly, the blindsight stimulus in both patients overlapped the border of preserved and absent signal, raising the possibility that fMRI sensitivity may simply reflect better resolution than perimetry at the border zones of field loss.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Two blindsight positive patients (P6, P8) showed retained fMRI signal in the blindsight test zone using both MP and pRF techniques, albeit not completely normal. This is consistent with previous studies ( Papanikolaou et al, 2014 ; Schneider et al, 2019 ; Sanchez-Lopez et al, 2020 ), and suggests that both methods can reveal preserved visual processing in hemianopia beyond SAP. Interestingly, the blindsight stimulus in both patients overlapped the border of preserved and absent signal, raising the possibility that fMRI sensitivity may simply reflect better resolution than perimetry at the border zones of field loss.…”
Section: Discussionsupporting
confidence: 93%
“…The study of Barbot et al (2020) also found that the strength of V1 activity in perimetrically blind regions predicted the amount of improvement following training, although there was little change in activity after training. In a similar vein, Schneider et al (2019) found that hemianopic patients showing fMRI activity in the visual cortex soon after their stroke showed less ganglion cell loss 6 months later. Understanding how this neural activity across the visual cortex relates to residual function may provide the basis for designing personalized rehabilitation programs that target spared visual pathways in patients.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Recovery after retinal thinning, as measured by OCT varies with pathology ( 41 43 , 45 , 55 , 59 , 60 ). Optic neuritis patients experience recovery of visual function with increasing VEP amplitudes despite continued loss of pRNFL thickness and significant optic nerve atrophy over 12 months ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Macular central subfield (CST), ganglion cell layer (GCL), inner plexiform layer (IPL) and pRNFL thickness measurements were processed independently by Carl Zeiss Meditec, Inc. Ganglion cell complex (GCC) thickness was calculated using the sum of GCL and IPL layers. Measures of retinal thickness were subsequently mapped onto visual space using an in-house pipeline implemented in MATLAB ( 45 ) and analyzed with respect to visual hemi-field (i.e., the averaged thickness of homonymous hemiretinas) for comparison with optic tract integrity. To account for contributions from nasal vs. temporal halves, retinal measures were weighted 53% contribution from nasal hemi-retina and 47% for temporal hemi-retina ( 46 ).…”
Section: Methodsmentioning
confidence: 99%